TESTING THE WEAK-FORM EFFICIENCY HYPOTHESIS IN THE UKRAINIAN STOCK MARKET VERSUS THOSE OF THE USA, RUSSIA, AND POLAND - Khrapko, Vladimir (Ekonomika, 2013)
Abstract. Objective. This empirical research was made to test a weak-form market efficiency of the stock market index in Ukraine as compared with other countries’ stock indexes. Data. Daily data were investigated for the period from August 2008 to October 2011. Methods. We applied different statistical tests to verify the hypothesis that the Ukrainian stock market follows a random walk. Main results. The main research findings are: the daily returns are not normally distributed; I.I.D. tests and the Kendall test support the random walk hypothesis. Test results on autocorrelation and variance stability were ambiguous. The reported results may be considered as the first approach to the further research on the efficiency of the Ukrainian securities markets.Key words: Ukraine, stock market, efficiency, test